Preparation method and application of vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material

By constructing vanadium-doped molybdenum nitride-nickel nitride-nickel nitride-nickel nitride-nickel nitride-nickel nitride-nickel junction nanomaterials, the existing alkaline electrolytic hydrogen production catalysts have been solved, and the effect of efficient hydrogen evolution and improving hydrogen production efficiency has been achieved.

CN119800430AActive Publication Date: 2025-04-11HEILONGJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510077680.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing catalysts for alkaline electrolytic hydrogen production are costly and have low catalytic activity, so large-scale hydrogen production applications cannot be achieved.

Method used

Construct a close-contact vanadium-doped molybdenum nitride-nickel nitride-nickel nitride-nickel nitride-nickel nitride three-phase heterojunction nanomaterial, and optimize the adsorption energy to the reaction intermediate and improve catalytic activity by regulating the interface charge distribution and introducing vanadium-regulating electronic structure.

Benefits of technology

It achieves efficient hydrogen evolution under alkaline conditions, reduces the overpotential and improves the electrocatalytic hydrogen production efficiency per unit mass, which is of practical application significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800430A_ABST
    Figure CN119800430A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material, and relates to a preparation method of a catalyst for hydrogen production by alkaline electrolysis of water. The invention aims to solve the problems of high cost and low catalytic activity of the existing catalyst for hydrogen production by alkaline electrolysis of water. According to the preparation method, a polyacid-nickel hydroxide nanosheet complex is obtained based on a molecular assembly principle by utilizing hydrogen bonds and electrostatic interaction between nickel hydroxide nanosheets and polyacids, and the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is prepared after nitridation treatment. The composite material has the advantages that components are tightly combined and uniformly distributed, the components are easy to regulate and control, the structure is stable, active sites are rich and the like, when the composite material is used as a catalyst for an electro-catalytic hydrogen evolution reaction, the required overpotential is only 34 mV when the current density is 10 mAcm <-2 > under the alkaline condition, and a foundation is laid for designing and preparing an electrochemical hydrogen evolution catalyst used under the alkaline condition in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a catalyst for producing hydrogen through alkaline water electrolysis. Background Art

[0002] As a secondary energy source with high energy density and environmental protection, hydrogen energy is expected to replace traditional fossil energy. However, hydrogen is currently mainly obtained through natural gas pyrolysis and coal gasification, accompanied by the release of carbon dioxide byproducts. Therefore, it is urgent to develop more environmentally friendly and efficient hydrogen production technologies. Alkaline water electrolysis to produce hydrogen has become the most promising way to prepare green hydrogen. At present, the precious metal Pt is the best HER catalyst, but its reserves are scarce and the price is high, which cannot be used for large-scale hydrogen production. Therefore, it is necessary to develop abundant, low-cost and efficient non-precious metal catalysts to replace Pt family catalysts, and to increase the number of active sites and intrinsic activity, and promote mass transfer and charge transfer to improve alkaline hydrogen evolution activity. Metal nitrides, especially molybdenum (nickel) nitrides, have Pt-like electronic structures, low costs, good conductivity, high catalytic activity, and high stability. They have been considered to be a very promising hydrogen evolution electrocatalyst, but their catalytic activity is far less than that of commercial Pt / C catalysts. Summary of the invention

[0003] The purpose of the present invention is to solve the problems of high cost and low catalytic activity of the existing catalyst for hydrogen production by alkaline water electrolysis, and to provide a preparation method and application of a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material.

[0004] The present invention constructs a closely contacted vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction nanomaterial, creates more active sites by regulating the interfacial charge distribution, and especially introduces vanadium with rich valence into the molybdenum nitride lattice, regulates its electronic structure, and optimizes the adsorption energy of the reaction intermediates, which is expected to obtain an alkaline and efficient hydrogen evolution catalytic material; at the same time, the construction of ultra-thin nanosheets with a large specific surface area and stable structure is conducive to providing more exposed active sites, and is helpful for mass transfer and charge transfer, and has attracted much attention. The present invention proposes to construct an ultra-thin sheet nanomaterial assembled with closely contacted vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction particles, which increases the number of active sites while improving the intrinsic activity, thereby reducing the overpotential, and then increasing the electrocatalytic hydrogen production efficiency per unit mass, which has practical application significance.

[0005] A method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is specifically completed by the following steps:

[0006] 1. dissolving nickel nitrate and urea in a mixed solution of deionized water and ethylene glycol to obtain solution I;

[0007] 2. transferring solution I to a hydrothermal reactor for hydrothermal reaction, centrifuging, washing and drying the suspension obtained after the hydrothermal reaction to obtain nickel hydroxide nanosheets;

[0008] 3. dissolving the polyacid in anhydrous ethanol to obtain solution II;

[0009] Fourth, dispersing nickel hydroxide nanosheets in anhydrous ethanol, and then adding solution II under stirring, stirring for a period of time to obtain a suspension; centrifuging, washing, and drying the obtained suspension to obtain a polyacid-nickel hydroxide nanosheet complex;

[0010] 5. Put the polyacid-nickel hydroxide nanosheet complex into a tubular furnace, introduce ammonia into the tubular furnace, and perform nitridation treatment in an ammonia atmosphere to obtain a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material.

[0011] Vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is used as a catalyst for hydrogen production by alkaline water electrolysis.

[0012] The invention utilizes hydrogen bonds and electrostatic effects between nickel hydroxide nanosheets and polyacids, obtains polyacid-nickel hydroxide nanosheet complexes based on the principle of molecular assembly, and obtains vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite materials after nitridation treatment; the obtained vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite materials have the advantages of close combination between components, uniform distribution, easy regulation of components, stable structure, rich active sites, etc., and are used as catalysts for electrocatalytic hydrogen evolution reaction, and the current density is 10 mA cm under alkaline conditions. -2 The required overpotential is only 34 mV, which lays the foundation for the future design and preparation of electrochemical hydrogen evolution catalysts for use under alkaline conditions.

[0013] In summary, the present invention also includes the following beneficial effects:

[0014] First, the present invention can realize controllable synthesis of composite materials by regulating variables such as material feeding ratio, stirring speed, heat treatment temperature and time;

[0015] Second, the present invention synthesizes a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material with a two-dimensional nanosheet assembly structure through simple intermolecular forces such as electrostatic adsorption; compared with the traditional preparation method, this method can obtain vanadium doping in a controllable way in one step, and helps to maintain a complete sheet structure, prevent agglomeration during the high-temperature formation of nitrides, and has the characteristics of being relatively simple and repeatable; and this method can be applied to the large-scale synthesis of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material;

[0016] 3. The vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared by the present invention has initially and effectively achieved the purpose of replacing the expensive precious metal Pt catalyst, and has important guiding significance for the design and practical commercial application of electrocatalytic alkaline water decomposition to produce hydrogen in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is an X-ray powder diffraction pattern of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0018] Figure 2 is a scanning electron microscope image of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0019] Figure 3 is a transmission electron microscope image of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0020] Figure 4 The linear sweep voltammetric curves are of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1, the molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 2, and the Pt / C catalyst. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material, which is specifically completed by the following steps:

[0022] 1. dissolving nickel nitrate and urea in a mixed solution of deionized water and ethylene glycol to obtain solution I;

[0023] 2. transferring solution I to a hydrothermal reactor for hydrothermal reaction, centrifuging, washing and drying the suspension obtained after the hydrothermal reaction to obtain nickel hydroxide nanosheets;

[0024] 3. dissolving the polyacid in anhydrous ethanol to obtain solution II;

[0025] Fourth, dispersing nickel hydroxide nanosheets in anhydrous ethanol, and then adding solution II under stirring, stirring for a period of time to obtain a suspension; centrifuging, washing, and drying the obtained suspension to obtain a polyacid-nickel hydroxide nanosheet complex;

[0026] 5. Put the polyacid-nickel hydroxide nanosheet complex into a tubular furnace, introduce ammonia into the tubular furnace, and perform nitridation treatment in an ammonia atmosphere to obtain a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material.

[0027] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that: the mass ratio of urea to nickel nitrate described in step 1 is 1:(1-3); the volume ratio of deionized water to ethylene glycol in the mixed solution of deionized water and ethylene glycol described in step 1 is 1:(0.5-1.5); the mass ratio of nickel nitrate described in step 1 to the volume ratio of the mixed solution of deionized water and ethylene glycol is (0.22g-0.66g):(20mL-60mL). The other steps are the same as those in specific embodiment 1.

[0028] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the temperature of the hydrothermal reaction in step 2 is 140° C. to 180° C., and the time of the hydrothermal reaction is 2 h to 8 h. The other steps are the same as those of specific embodiment 1 or 2.

[0029] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the polyacid described in step 3 is phosphomolybdic acid, phosphomolybdic acid, ammonium molybdate or silicomolybdic acid. The other steps are the same as those of specific embodiments 1 to 3.

[0030] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass ratio of the polyacid to anhydrous ethanol in step 3 is 1:(200-600). The other steps are the same as those of specific embodiments 1 to 4.

[0031] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that the stirring speed in step 4 is 300 rpm to 600 rpm, and the stirring time is 6 h to 24 h. The other steps are the same as those of specific implementation methods 1 to 5.

[0032] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the mass ratio of the nickel hydroxide nanosheets to anhydrous ethanol in step 4 is 1:(400-500); the mass ratio of the nickel hydroxide nanosheets to the polyacid in solution II in step 4 is 5:(1-4). The other steps are the same as those in specific embodiments 1 to 6.

[0033] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the nitriding process described in step 5 is: heating from room temperature to 400°C to 500°C at a heating rate of 1°C / min to 5°C / min, and nitriding at 400°C to 500°C for 2h to 4h. The other steps are the same as those of specific embodiments 1 to 7.

[0034] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the flow rate of the ammonia gas in step 5 is 10 mL / min to 30 mL / min. The other steps are the same as those of specific embodiments 1 to 8.

[0035] Specific embodiment ten: This embodiment is to use a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material as a catalyst for hydrogen production by alkaline water electrolysis.

[0036] The following examples are used to verify the beneficial effects of the present invention:

[0037] Example 1: A method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material (V-MoN / Ni3N), which is specifically completed by the following steps:

[0038] 1. Dissolve 0.52 g nickel nitrate and 0.22 g urea in a mixed solution of 16 mL deionized water and 24 mL ethylene glycol to obtain solution I;

[0039] 2. transferring solution I to a hydrothermal reactor for hydrothermal reaction, centrifuging the suspension obtained after the hydrothermal reaction, washing with deionized water, and drying to obtain nickel hydroxide nanosheets;

[0040] The temperature of the hydrothermal reaction in step 2 is 140° C., and the time of the hydrothermal reaction is 4 h;

[0041] 3. Dissolve 0.05 g of polyacid in 20 mL of anhydrous ethanol to obtain solution II;

[0042] The polyacid described in step 3 is a phosphomolybdicvanadic heteropoly acid;

[0043] Fourth, 0.1 g of nickel hydroxide nanosheets were dispersed in 40 mL of anhydrous ethanol, and then solution II was added under stirring, and the mixture was stirred for 12 h at a stirring speed of 500 rpm to obtain a suspension by electrostatic adsorption; the obtained suspension was centrifuged, washed with deionized water, and dried to obtain a polyacid-nickel hydroxide nanosheet complex;

[0044] 5. placing the polyacid-nickel hydroxide nanosheet composite into a tubular furnace, introducing ammonia into the tubular furnace, and performing nitridation treatment under an ammonia atmosphere to obtain a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material (V-MoN / Ni3N);

[0045] The nitriding process described in step 5 is: heating from room temperature to 450°C at a heating rate of 2°C / min, and nitriding at 450°C for 3h;

[0046] The flow rate of ammonia gas described in step 5 is 20 mL / min.

[0047] The preparation method of the phosphorus molybdenum vanadium heteropoly acid described in step 3 of Example 1 is specifically completed according to the following steps:

[0048] ①, dissolve 12.2g of sodium metavanadate in 50mL of hot water at 80°C to obtain a sodium metavanadate aqueous solution;

[0049] ②, dissolve 3.55g of disodium hydrogen phosphate in 50mL of water to obtain a disodium hydrogen phosphate aqueous solution;

[0050] ③. Add the sodium hydrogen phosphate aqueous solution to the sodium metavanadate aqueous solution, cool to room temperature, and then add 2.5 mL of 98% concentrated sulfuric acid to obtain an orange-red solution;

[0051] ④, 60.5g sodium molybdate was dissolved in 100mL water to obtain a sodium molybdate solution; the sodium molybdate solution was added dropwise to the orange-red solution, and then 42.5mL of 98% concentrated sulfuric acid was added, cooled to room temperature, and then an appropriate amount of ether was added for extraction, leaving the middle layer, and finally placed in a fume hood until the ether was completely evaporated to obtain an orange sample, which is phosphorus molybdenum vanadium heteropoly acid (H5PV2Mo 10 O 40 ).

[0052] Figure 1 is an X-ray powder diffraction pattern of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0053] from Figure 1 It can be seen that 36.21° and 49.01° belong to the (200) and (202) crystal planes of MoN respectively; 42.11° belongs to the (002) crystal plane of Ni3N; 44.51°, 51.85° and 76.37° belong to the (111, (200) and (220) crystal planes of Ni respectively.

[0054] Figure 2 is a scanning electron microscope image of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0055] from Figure 2 It can be seen that the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is a two-dimensional lamellar structure, composed of nanosheets composed of particles with a diameter of about 30nm, and has a porous structure.

[0056] Figure 3 is a transmission electron microscope image of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1;

[0057] from Figure 3It can be seen that the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is assembled from small particles, and the thin film shows a rich porous structure. High-resolution transmission electron microscopy images show that the interplanar spacing of 0.222nm belongs to the (200) crystal plane of molybdenum nitride, the interplanar spacing of 0.213nm belongs to the (002) crystal plane of nickel nitride, and the interplanar spacing of 0.204nm belongs to the (111) crystal plane of nickel, proving the successful construction of the multi-phase heterojunction.

[0058] Embodiment 2: The preparation method of the molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material (MoN / Ni3N) is specifically completed by the following steps:

[0059] 1. Dissolve 0.52 g nickel nitrate and 0.22 g urea in a mixed solution of 16 mL deionized water and 24 mL ethylene glycol to obtain solution I;

[0060] 2. transferring solution I to a hydrothermal reactor for hydrothermal reaction, centrifuging the suspension obtained after the hydrothermal reaction, washing with deionized water, and drying to obtain nickel hydroxide nanosheets;

[0061] The temperature of the hydrothermal reaction in step 2 is 140° C., and the time of the hydrothermal reaction is 4 h;

[0062] 3. Dissolve 0.05 g of polyacid in 20 mL of anhydrous ethanol to obtain solution II;

[0063] The polyacid described in step 3 is phosphomolybdic acid;

[0064] Fourth, 0.1 g of nickel hydroxide nanosheets were dispersed in 40 mL of anhydrous ethanol, and then solution II was added under stirring, and the mixture was stirred for 12 h at a stirring speed of 500 rpm to obtain a suspension by electrostatic adsorption; the obtained suspension was centrifuged, washed with deionized water, and dried to obtain a polyacid-nickel hydroxide nanosheet complex;

[0065] 5. placing the polyacid-nickel hydroxide nanosheet composite into a tubular furnace, introducing ammonia into the tubular furnace, and performing nitridation treatment under an ammonia atmosphere to obtain a molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material (MoN / Ni3N);

[0066] The nitriding process described in step 5 is: heating from room temperature to 450°C at a heating rate of 2°C / min, and nitriding at 450°C for 3h;

[0067] The flow rate of ammonia gas described in step 5 is 20 mL / min.

[0068] Figure 4The linear sweep voltammetric curves of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1, the molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 2, and the Pt / C catalyst are as follows: 2.5 mg of the catalyst sample to be tested is weighed and dispersed in 0.5 mL of a mixed solution (including: 25 μL of a 5% Nafion solution, a water / ethanol volume ratio of 1:1), and ultrasonically dispersed for 1 hour to form a concentration of 5 mg mL -1 The uniform dispersion is evenly dropped on the nickel foam and the electrochemical test can be carried out after drying. In the electrocatalytic hydrogen evolution test, the carbon rod is used as the counter electrode, the Hg / HgO electrode is used as the reference electrode, the nickel foam coated with the catalyst to be tested is used as the working electrode, and the electrolyte is 1M KOH. The linear cyclic voltammetry scan test has a scan rate of 5mV s -1 , scanning range -1 V ~ 0 V. All potentials were calibrated with a reversible hydrogen electrode (RHE).

[0069] from Figure 4 It can be seen that the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared in Example 1 as a catalyst for alkaline electrocatalytic hydrogen evolution has a current density of 10 mA cm -2 The required overpotential is only 34 mV, which is very close to the 29 mV@10 mA cm of commercial Pt / C. -2 The molybdenum nitride-nickel nitride-nickel three-phase heterojunction prepared in Example 2 was -2 The overpotential is 54 mV. The above results show that vanadium doping can effectively improve the catalytic activity of the material. Especially when the current density is greater than 30 mA cm -2 When the catalyst is prepared, the catalytic activity of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is significantly better than that of the commercial 20% Pt / C catalyst, indicating that the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material with large specific surface area and stable structure plays an important role in improving the catalytic activity.

Claims

1. A method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material, characterized in that The preparation method is specifically completed according to the following steps:

1. dissolving nickel nitrate and urea in a mixed solution of deionized water and ethylene glycol to obtain solution I; 2. transferring solution I to a hydrothermal reactor for hydrothermal reaction, centrifuging, washing and drying the suspension obtained after the hydrothermal reaction to obtain nickel hydroxide nanosheets; 3. dissolving the polyacid in anhydrous ethanol to obtain solution II; Fourth, dispersing nickel hydroxide nanosheets in anhydrous ethanol, and then adding solution II under stirring, stirring for a period of time to obtain a suspension; centrifuging, washing, and drying the obtained suspension to obtain a polyacid-nickel hydroxide nanosheet complex; 5. Put the polyacid-nickel hydroxide nanosheet complex into a tubular furnace, introduce ammonia into the tubular furnace, and perform nitridation treatment in an ammonia atmosphere to obtain a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material.

2. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The mass ratio of urea to nickel nitrate described in step one is 1:(1-3); the volume ratio of deionized water to ethylene glycol in the mixed solution of deionized water and ethylene glycol described in step one is 1:(0.5-1.5); the mass ratio of nickel nitrate described in step one to the volume ratio of the mixed solution of deionized water and ethylene glycol is (0.22g-0.66g):(20mL-60mL).

3. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The temperature of the hydrothermal reaction in step 2 is 140° C. to 180° C., and the time of the hydrothermal reaction is 2 h to 8 h.

4. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The polyacid described in step 3 is phosphomolybdic acid, phosphomolybdic acid, ammonium molybdate or silicomolybdic acid.

5. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The mass ratio of the polyacid to anhydrous ethanol described in step 3 is 1:(200-600).

6. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The stirring speed in step 4 is 300 rpm to 600 rpm, and the stirring time is 6 h to 24 h.

7. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The mass ratio of the nickel hydroxide nanosheets described in step 4 to anhydrous ethanol is 1:(400-500); the mass ratio of the nickel hydroxide nanosheets described in step 4 to the polyacid in solution II is 5:(1-4).

8. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The process of the nitriding treatment described in step five is: heating from room temperature to 400°C to 500°C at a heating rate of 1°C / min to 5°C / min, and nitriding at 400°C to 500°C for 2h to 4h.

9. The method for preparing a vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material according to claim 1, characterized in that The flow rate of the ammonia gas described in step 5 is 10 mL / min to 30 mL / min.

10. Application of the vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material prepared by the preparation method according to claim 1, characterized in that Vanadium-doped molybdenum nitride-nickel nitride-nickel three-phase heterojunction composite material is used as a catalyst for hydrogen production by alkaline water electrolysis.

Citation Information

Patent Citations

  • Preparation method and application of molybdenum-doped nickel nitride electrode material

    CN115995352A

  • Preparation method of alkaline electrolytic water hydrogen evolution electrocatalyst based on polyacid molecule interface engineering strategy

    CN118835276A